2013
DOI: 10.7567/jjap.52.07hc11
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Sound Field Analysis Using Compact Explicit-Finite Difference Time Domain Method with Graphics Processing Unit Cluster System

Abstract: In this study, the compact explicit-finite difference time domain (CE-FDTD) method is applied to the three-dimensional sound field analysis to reduce computer resources. There are various derivative schemes in the CE-FDTD method. They are first examined theoretically to evaluate the numerical accuracy. As a theoretical result, it is found that the interpolated wide band (IWB) scheme has the widest bandwidth in which the cut-off frequency is in agreement with the Nyquist frequency. The calculation performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In this paper, a ¼ 1=4 is used as the interpolated wide-band (IWB) scheme. The sound field analysis tool based on the CE-FDTD method has already been well verified in our previous researches [19][20][21][22][23].…”
Section: Theorymentioning
confidence: 66%
See 1 more Smart Citation
“…In this paper, a ¼ 1=4 is used as the interpolated wide-band (IWB) scheme. The sound field analysis tool based on the CE-FDTD method has already been well verified in our previous researches [19][20][21][22][23].…”
Section: Theorymentioning
confidence: 66%
“…In this paper, the compact explicit finite-difference time domain (CE-FDTD) method [18][19][20][21][22] is applied to the moving sound source and receiver, while proposed methods can also be applied to the standard FDTD method [1]. The CE-FDTD method is a high accuracy version of the standard FDTD method and is good at large-scale sound field analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, general-purpose graphic processing units (GPGPUs) and FPGAs have been applied to speed up the arithmetic operations in sound rendering systems [13][14][15][16][17][18][19][20][21][22]. Although GPGPU-based solutions achieve high computation performance through increasing system threads, the input and output interfaces are more difficult to customize according to applications.…”
Section: Introductionmentioning
confidence: 99%
“…The movement toward applying GPU to scientific computing has been ongoing since 2005 [1]. A number of studies have reported the application of GPU [2][3][4] to largescale and long-time acoustic simulation for finite-difference time-domain (FDTD) methods [5][6][7]. On the other hand, the first generation of Intel MIC architecture is newer than GPU because it was only released in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we perform software optimizations known in the field of high-performance computing (HPC) [9] to reveal the attainable performance of the Intel MIC architecture. The acoustic FDTD schemes we examined are the standard FDTD(2,2) [10], FDTD(2,4) [11], and WE (Wave Equation) -FDTD(2,2) [3,12] schemes.The purpose of this study is to evaluate the performance of acoustic FDTD schemes on the Intel MIC architecture and to reveal the attainable performance by performing software optimizations. …”
mentioning
confidence: 99%